Studies on Structure and Elasto-Mechanical Properties of Suvin Cotton Fibre - Manju, V. V.; Divakara, S.; Somashekar, R. (Journal of Scientific Research, 2020)
The comprehensive elastic properties of Suvin cotton fibre have been estimated. The Linked Atom Least Square method (LALS) technique has been employed to compute the structural properties using the X-ray diffraction data. Using Treloar’s assumptions the elastic stiffness matrix |Cij| has been calculated, then by utilizing the Voigt theory the elastic constants like Young’s modulus (E), Bulk modulus (K), Shear modulus (G), Poisson’s ratio (ν) and linear compressibility (β) have been estimated. Further, the experimental results of elastic constants are obtained and compared with the computed results and a broad correlation between them has been observed. ELATE web application tool is used to obtain the 3-dimensional images of variation of elastic constants along their spatial axes. From these figures an attempt has been made to explain the anisotropic mechanical property with respect to directional dependent Young’s modulus (E) and Shear modulus properties (G).